MEDIA KOMUNIKASI TRADISIONAL PADA MASYARAKAT JAWA - Rita Istari (BRIN, 2001)
The Indonesian nation in general and the Javanese in particular have had various abilities as a frame of reference that lasted for generations. Thus the various capabilities that exist today are actually only products of the